Risk Factors for the Spread of Leptospira sp. in Rats Using Success Trap and iiPCR Methods in Probolinggo Harbor - Yudhistiro Angga Kurniawan; Enny Suswati; Mei Syafriadi (Poltekkes Kemenkes Surabaya, 2025)
This study aimed to identify the distribution of rats and environmental risk factors associated with the spread of Leptospira sp. in Probolinggo Harbor using success trap and iiPCR methods. A total of 150 traps were deployed across 66 strategic locations around the harbor, capturing 19 rats, with a rat capture rate of 4.2%. Among the captured rats, 21.05% tested positive for Leptospira sp., with Rattus tanezumi constituting 75% of the infections and Rattus norvegicus accounting for the remaining 25%. Path analysis (SmartPLS 4.0) revealed significant associations between gutter conditions, vegetation, humidity, and signs of rat activity with the presence of Leptospira sp. Environmental factors such as gutter conditions, temperature, humidity, and vegetation were found to significantly influence the prevalence of Leptospira sp., with Rattus tanezumi identified as the primary vector, particularly in locations with open waste systems or abundant vegetation. These findings highlight the critical role of environmental factors in the transmission of leptospirosis, emphasizing the need for targeted environmental management strategies, including rodent control programs and improvements in sanitation, to mitigate risks in harbor areas.